The Effect of Online Learning VS Face-To-Face Learning on Student Learning Motivation Post the Covid - 19 Pandemic at Schools and Colleges - Jainal Abidin; Erwina Azizah HASIBUAN; Mahdalia HARAHAP (RADINKA JAYA UTAMA PUBLISHER, 2023)
This study aims to look at a comparative description of learning motivation during online learning and face-to-face learning after the end of the Covid pandemic. The Covid-19 disease outbreak is a situation beyond predictions that has brought urgent changes in various sectors of activity including in the world of education. The development of the virus quickly spread throughout the world. This affects policies to be implemented in the world of education by changing learning that has to come to class to be sufficient at home. With the government's advice to stay at home and always keep a distance and learning is done online so that it has a decreasing impact on learning outcomes. This activity has been going on for about 2 years which has resulted in a drastic decline in learning motivation. Online learning is less able to motivate students whose interactions are online using zoom, Google Meet, Google Classroom and WhatsApp between educators and students virtually. To increase learning motivation, namely by re-enacting face-to-face learning at school. At this time, face-to-face learning has been allowed again, so that this research can be carried out. This research needs to be done to see changes in student motivation. Where it is hoped that there will be a comparison of learning motivation, where learning motivation by face-to-face learning increases when compared to online learning.